TELAAH KRITIS TERHADAP PERIODISASI KODIFIKASI MUḤAMMAD ḤUSAYN AL-DHAHABĪ DALAM AL-TAFSĪR WA AL-MUFASSIRŪN - Umam, Muhammad Fithri (AL ITQAN: Jurnal Studi Al-Qur'an, 2016)
This paper critically analyzes the history of the development of Quranic exegesis in the codification era of the periodization by Muḥammad Ḥusayn al-Dhahabī in his monumental work, al-Tafsīr wa al-Mufassirūn. al-Dhahabī classifies the exegesis codification era into five stages (al-khaṭwah. According to him, the compilation and codification of exegesis which covers verse by verse, chapter by chapter, is compiled separately from hadith chapters and systematically according to the order of the book (mushaf) were initially practiced in the era of tābi‟ tābi'i al-tabi'īn, such as Ibnu Mājah (d. 310 AH), and other scholars after him. This paper aims at testing the accuracy of this periodization of al-Dhahabīby using verificative-qualitative analysis including the verification of the source authenticity and credibility. This paper also makes use of the information in several tārīkh, tarājim, ṭabaqāt books which explore many historical events to criticize this periodization mapped by al-Dhahabî.